Double-Controlled Release of Poorly Water-Soluble Paliperidone Palmitate from Self-Assembled Albumin-Oleic Acid Nanoparticles in PLGA in situ Forming Implant - Yu Y (Dove Medical Press, 2021)
Yongjun Yu,1 Hai V Ngo,1 Gang Jin,1 Phuong HL Tran,2 Thao TD Tran,3,4 Van Hong Nguyen,5 Chulhun Park,6 Beom-Jin Lee1 1College of Pharmacy, Ajou University, Suwon, 16499, Republic of Korea; 2Deakin University, School of Medicine, Geelong, Australia; 3Institute of Research and Development, Duy Tan University, Danang, 550000, Vietnam; 4The Faculty of Pharmacy, Duy Tan University, Danang, 550000, Vietnam; 5Pharmaceutical Engineering Laboratory, Biomedical Engineering Department, International University, Vietnam National University, Ho Chi Minh City, 70000, Vietnam; 6Faculty of Pharmacy and Pharmaceutical Sciences, University of Alberta, Edmonton, Alberta, CanadaCorrespondence: Beom-Jin LeeBioavailability Control Laboratory, College of Pharmacy, Ajou University, Suwon, 16499, Republic of KoreaTel +82312193442Fax +82312193435Email bjl@ajou.ac.krPurpose: To investigate the effects of solvents on the formation of self-assembled nanonization of albumin-oleic acid conjugates (AOCs) using a solvent exchange mechanism for the construction of in situ forming implants (ISFI).Methods: A poorly water-soluble drug, paliperidone palmitate (PPP), was chosen as the model drug. AOC was synthesized with the 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) reaction. Dichloromethane, tetrahydrofuran, ethanol, N-methyl-2-pyrrolidone, dimethyl sulfoxide, and deionized water were selected to investigate the formation of self-assembled AOC nanoparticles (AONs). The volume ratios of organic solvents against water could determine the miscibility, injectability, and in situ nanonizing capability without aggregation.Results: As the polarity of the organic solvents increased, the AONs exhibited a spherical shape, and the larger the volume of the solvent, the smaller the size of the AONs. To use AOC in ISFI for controlled release of PPP, poly(d,l-lactide-co-glycolide) (PLGA) was combined with the AOC in 2 mL of N-methyl-2-pyrrolidone and water solution (1.8/0.2 ratio). The release rates of all formulations exhibited similar curve patterns overall but were more controlled in decreasing order as follows: AOC, PLGA, and AOC/PLGA for 14 days.Conclusion: A combined formulation of AOC and PLGA was found to effectively control the initial burst release of the drug.Keywords: albumin-oleic acid conjugate, self-assembled nanonization, solvent type, in situ forming implant, solvent exchange, controlled release